E-Learning as a Response to COVID-19 Pandemic: A preliminary study on College Students - Siska Ayu Kartika (Universitas Muhammadiyah Sidoarjo, 2021)
There is a dilemma of accepting the new educational system, that we know as “e-learning” by students within educational institutions. We have to replace face-to-face education with distance education in response to the COVID-19. This form of distance education, e-learning, differs from conventional education: being suddenly, unreadily and forcefully implemented. This study examined and assessed the impact of e-learning to college students, during pandemic. An online survey was conducted amongst some college students in the Mechanical Engineering Dept, at Universitas Balikpapan using a purposive sampling technique. Data were analyzed using Partial Least Square - Structural Equation Modelling (PLS-SEM). The result of this study has confirmed the positive of direct effect variables (attitude, affect and motivation; perceived behavioral intention (ease of use technology, accessibility and cognitive engagement). This study suggests relevant parties to the education system, to improve the implementation of e-learning systems.